THE EFFECT OF FIRM SIZE, PROFITABILITY, LEVERAGE, SALES GROWTH AND CAPITAL INTENSITY ON TAX AVOIDANCE - Aldo Suhartono; Agustin Ekadjaja (Graduate Program of Universitas Tarumanagara, 2024)
This study aims to determine and analyze the effect of Company Size, Profitability, Leverage, Sales Growth, Capital Intensity and Company Age on tax avoidance in non-cyclical companies listed on the Indonesia Stock Exchange in the 2020-2022 period. The sampling technique uses purposive sampling in the form of secondary data taken from www.idx.co.id or the company's official website. The number of samples in this study were 78 samples. The data analysis method used is descriptive statistics, classical assumption test, and multiple linear regression analysis using the SPSS (Statistical Package for Social Science) application. The results of the study show that firm size has a negative effect on tax avoidance. This research is expected to provide insights that influence the practice of tax avoidance in Indonesia.